Bridging the “chasm”: identifying factors to accelerate the adoption of plant-based meat alternative products - Flint, Megan; Bowles, Simon; Paxman, Jenny R.; Lynn, Anthony (Frontiers in Sustainable Food Systems, 2025)
IntroductionPlant-based meat alternatives (PBMAs) present a promising pathway towards a more sustainable and healthier food system. However, the rate of adoption of PBMA products must accelerate to meet global health and sustainability targets.MethodsA cross-sectional questionnaire categorised respondents (n = 325) according to Roger’s Diffusion of Innovation and measured perceptions of, and key food choice motives (FCM) and barriers influencing the adoption of PBMAs within Innovators/Early Adopters (11.7%), Early Majority (35.9%), Late Majority (35.6%) and Laggards (16.8%).ResultsOur findings revealed plant-based burgers, ‘chicken’ and sausage products were perceived more favourably in Innovators/Early Adopters and Early Majority versus Late Majority and Laggards. Relative importance of FCM and barriers to adoption of PBMAs varied between groups. However, both the Early Majority and Late Majority demonstrated identical ranked priority for motives (sensory appeal, health, and affordability) and barriers (degree of processing, cost, and taste).DiscussionThese groups represent over two thirds of the sample population and therefore jointly targeting these groups with evidence-informed strategies has the potential to increase the rate of adoption of PBMA products. This highlights the need for manufacturers to address the sensorial and health quality of PBMA products whilst also considering the degree of processing and their affordability. Such evidence-based manufacturing practice may facilitate sustainable behaviour change across the wider population and support the environmental and public health agenda.